2017
DOI: 10.1080/07399332.2017.1325487
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on perception of body weight of women from different socioeconomic levels

Abstract: The purpose of the study was to evaluate perception of body weight (PBW) of women who live in two different regions of the Antalya provincial center in Turkey with different socioeconomic status (SES) and whose ages range from 50 to 65. A cross-sectional survey was conducted. Association with PBW was investigated using multiple logistic regression analyses; correct PBW of women in middle SES was 0.28 times more than those in upper-middle and upper SES. Health professionals should take unemployed women with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…On the other hand, it was seen that a distorted perception in the way of underestimation was strikingly more common among adults classified as having normal BMI or being overweight or obese. Previous studies have similarly indicated that adults have distorted perceptions of their body weight 19,40–42. In another study that had been conducted in the same area, it was reported that individuals in lower socioeconomic groups, retirees, and women with high BMIs had more distorted perceptions about their actual BMI values 19.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…On the other hand, it was seen that a distorted perception in the way of underestimation was strikingly more common among adults classified as having normal BMI or being overweight or obese. Previous studies have similarly indicated that adults have distorted perceptions of their body weight 19,40–42. In another study that had been conducted in the same area, it was reported that individuals in lower socioeconomic groups, retirees, and women with high BMIs had more distorted perceptions about their actual BMI values 19.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have similarly indicated that adults have distorted perceptions of their body weight. 19,[40][41][42] In another study that had been conducted in the same area, it was reported that individuals in lower socioeconomic groups, retirees, and women with high BMIs had more distorted perceptions about their actual BMI values. 19 Our study findings indicate that distorted perceptions of BMI values will need to be improved if obesity is to be prevented in adults.…”
Section: E270mentioning
confidence: 97%
See 1 more Smart Citation
“…Accurate perception of body weight is influenced by a number of factors, many of which affect actual weight, including age, gender, family, societal values, ethnicity, education level and socio-economic status (SES) [4,[17][18][19][20][21]. Cognitive functioning, particularly executive functioning, has also been linked to excess weight [22][23][24][25] as well as to accurate perception of body weight [26].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies conducted in Turkey determined that adults underestimated their risks and risk factors of CVD. [14][15][16] The Omaha System is a classification system used in public health nursing interventions. When making interventions, the health care supervision-related diagnosis is considered within the scope of diagnoses related to health behaviors.…”
mentioning
confidence: 99%